RESISTANCE AND RESILIENCE IN CHANGING INDONESIA: The Political Struggle and Movement of Hidayatullah - Adiyono, Adiyono; Abdurrohim, Abdurrohim (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2024)
This article seeks to endeavors and strategies of an Islamic organization, Hidayatullah, to survive in changing political regimes in the New Order to Reformation period of Indonesia. It was established as an Islamic educational and dakwah (Islamic proselytizing) institution in Balikpapan, East Kalimantan, in 1973. Despite socio-political changes in the country, it has expanded to several provinces in Indonesia which transformed it to become the largest Islamic educational institution with 402 branches of Islamic schools. The organization focuses its activities on Islamic education and dakwah through various ways including printed media such as Suara Hidayatullah magazine, distributed weekly to its branches, mosques, and schools. Based on a literature review of Suara Hidayatullah magazine and interviews with Hidayatullah prominent figures, this article delves into the struggles and movement of Hidayatullah through its dynamics and transformation in socio-political changes in Indonesia. This article argued that in political dynamics and transformation within Hidayatullah organization show the resistance and resilience to survive in the socio-political crisis of Suharto’s New Order era (1966-1998), which discriminated against Islam as a political ideology and in the aftermath of reformation. One of the strategies to comply with the political repressions is to declare Hidayatullah as an Islamic organization like Nahdlatul Ulama (NU) and Muhammadiyah in 2000. This transformation process proves Hidayatullah’s strategic foresight and adaptability in socio-cultural and political changes.